Effects of Multi-walled Carbon Nanotubes (MWCNTs) and Integrated MWCNTs/SiO2 Additives on Polymeric PVDF Membrane for Membrane Distillation - Zhou, Rufan (Université d'Ottawa / University of Ottawa, 2018)
Multi-walled carbon nanotubes (MWCNTs) and integrated MWCNTs/ SiO2 nanoparticles (NPs) were loaded as additives into nanocomposite polyvinylidene fluoride (PVDF) membranes fabricated via phase inversion methods, and the effects of these additives on the structure and vacuum membrane distillation (VMD) performance of the membranes have been studied. With an appropriate amount of MWCNTs (2 wt.% to PVDF) blended into the membrane, VMD performance of membrane was improved significantly due to higher membrane porosity, contact angle and surface roughness without extreme compromise of liquid entry pressure of water (LEPw), which could reach up to 72 psi. Further integration of MWCNTs with a small amount of SiO2 nanoparticles (NPs) showed a synergic effect resulting in further improvement of VMD flux due primarily to the increase in surface pore size. When the amount of SiO2 NPs additive was large, the effects of NPs dominates the VMD performance. However, the asymmetric structure of PVDF membrane disappears, which exercises an unfavourable effect on VMD performance. All fabricated membranes exhibited a great desalination potential with extremely high salt rejection (>99.98%). The incorporation of MWCNTs did not improve the tensile properties of the membrane.
Keywords: Multi-walled Carbon Nanotubes; Polymeric PVDF Membrane; integrated MWCNTs/ SiO2 nanoparticles